1983
DOI: 10.1161/01.str.14.6.948
|View full text |Cite
|
Sign up to set email alerts
|

Middle cerebral artery occlusion as a cause of isolated subcortical infarction.

Abstract: SUMMARY We report two patients with large subcortical hemispheric infarctions, located in areas prone to the development of lacunes, who had occlusion of the middle cerebral artery demonstrated by arteriography. The cortical vessels were perfused by leptomeningeal collaterals. We suggest that large vessel arterial disease should be considered as a possible etiology of large subcortical infarctions and propose that the term lacune should not be used in cases in which neither the size nor the pathophysiologic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 18 publications
0
29
0
Order By: Relevance
“…Fukuyama et al 105 (1983) studied LMA by nuclear medicine techniques and concluded that cortical infarction occurs in cases with inadequate development of LMA despite an angiographically normal circle of Willis. In this way, he introduced the concept of vascular dynamics, which was also observed by Adams 106 (1983) and Hasegawa 107 (1992) and explained by Naritomi et al 108 (1985). Bozzao et al 109 (1989) stated that the presence of LMA in the late phases of an ischemic lesion does not indicate presence in the early phases.…”
Section: To Presentmentioning
confidence: 83%
“…Fukuyama et al 105 (1983) studied LMA by nuclear medicine techniques and concluded that cortical infarction occurs in cases with inadequate development of LMA despite an angiographically normal circle of Willis. In this way, he introduced the concept of vascular dynamics, which was also observed by Adams 106 (1983) and Hasegawa 107 (1992) and explained by Naritomi et al 108 (1985). Bozzao et al 109 (1989) stated that the presence of LMA in the late phases of an ischemic lesion does not indicate presence in the early phases.…”
Section: To Presentmentioning
confidence: 83%
“…Our model should prove useful for studying both permanent and temporary regional experimental cerebral ischemia to simulate cerebrovascular occlusive disease in humans 22 and for evaluating the eflFects of reperfusion and other physiological manipulations or treatments.…”
Section: Discussionmentioning
confidence: 99%
“…37 Fifth, in our subjects large subcortical infarcts were generally associated with involvement of cortical clinical features, but large subcortical lesions presenting as a pure motor hemiplegia and associated with MCA occlusion have been reported on rare occasions. 38 Sixth, our series was retrospective, and although the clinical notes were detailed and of high standards, no formal protocol for HCF testing was used other than those 64 Stroke Vol20, No 1, January 1989 features generally included in a careful neurologic examination. In some patients late CT scans were not obtained.…”
Section: Discussionmentioning
confidence: 99%